(untitled) (Bangladesh Journal of Plant Taxonomy, 2022)
This study was conducted to discover wide spectrum of endophyte diversity from the Zingiber officinale Rosc. Endophytic fungi were obtained from different plant tissues. All the isolated strains were identified up to genus level following described colony morphology. The recognized five different morphotypes were subjected to sequence analysis of internal transcribed spacer (ITS) gene. Fusarium proliferatum, Fusarium solani and Cladosporium cladosporoides were identified based on comparison of the BLAST results and phylogenetic identification. The presented study provides the comprehensive explanation of the interrelation of morphological and molecular homologies for the identification of the prospective fungi. Bangladesh J. Plant Taxon. 29(2): 361-371, 2022 (December)